Active Thermal Control for Lifetime Equalization in CSI7-based Modular Photovoltaic Integration System - Peng Q.; Buticchi G.; Migliazza G.; Tan N.M.L.; Guenter S.; Carfagna E.; Fidone G.L. (Institute of Electrical and Electronics Engineers Inc., 2024)
The current source converter has been proved to be an advantageous architecture for a wide number of applications, i.e. renewable energy or aerospace, where voltage boost operation and high reliability are required. A modified current source inverter (CSI7) topology has been adopted with the objective of reducing the switching losses and ensure soft-switching operation, thus addressing the long-standing drawbacks of the current source topologies compared to the voltage source ones. This paper addresses a custom modulation strategy that aims at controlling the lifetime of the power devices which compose the power electronics by modifying the generation of the zero current state. Given the unequal stress of the power devices and the possibility that different types of devices being adopted, this solution allows for an extended reliability of the power electronics system. Hardware-in-the-loop simulations with a CSI7-based photovoltaic (PV) integration system confirm the validity of the proposed solution. 2023 IEEE.